2018
DOI: 10.1111/1346-8138.14594
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the skin microbiota in a healthy Chinese population

Abstract: The skin microbiota is an inseparable component of the skin barrier structure, which participates in the stabilization or impairment of the barrier function as well as the development of many skin diseases. To characterize the normal skin microbiota and its association with skin sites, age and sex, we recruited 50 volunteers divided into children, adolescents, young adults, middle-aged adults and the elderly. The skin sites consisted of cheeks, volar forearms (representing dry environments) and upper back (rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
(72 reference statements)
7
28
0
Order By: Relevance
“…Age is known to influence the skin microbiota composition. The relative abundance of C. acnes in our under 20 age group (mean age: 14) was lower than that of the over 20 age group (mean age: 26) (19% vs. 33%), which is compatible with the study results by Zhai et al [31]. In this particular study, C. acnes evolved with age, showing the lowest abundance in childhood (four to six years), a dramatic increase at puberty (11-13 years), a peak in young adults (25-34 years), and a subsequent decline with age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Age is known to influence the skin microbiota composition. The relative abundance of C. acnes in our under 20 age group (mean age: 14) was lower than that of the over 20 age group (mean age: 26) (19% vs. 33%), which is compatible with the study results by Zhai et al [31]. In this particular study, C. acnes evolved with age, showing the lowest abundance in childhood (four to six years), a dramatic increase at puberty (11-13 years), a peak in young adults (25-34 years), and a subsequent decline with age.…”
Section: Discussionsupporting
confidence: 92%
“…The influence of sex on the composition and diversity of the bacterial communities was relatively small compared to age. Still, we found a higher relative abundance of Pseudomonas in females, which is in line with findings from a prior study [31]. This variation is thought to rise from the difference in sebum levels as well as the habitual use of cosmetics and moisturizers among the female population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although a large study of 2963 patients with chronic wounds indicated no statistically significant difference in wound microbial communities among different diagnostic wound types, demographic data, gender, and age have been shown to affect microbial composition in smaller human studies . Elderly populations have exhibited increased microbial diversity and decreased skin‐site selectivity . Comorbid conditions may also affect wound healing and microbial status.…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
“…The stratum corneum (Sc) is the outermost layer of the epidermis and is required for barrier function to retain moisture in the skin and protect the skin from external invasion (1,2). If the barrier integrity or function is disrupted, water in the dermis and epidermis will be lost, the balance of the skin microecology will be disrupted (3), and hostile factors from the external environment will easily invade the skin, leading to skin ageing and the occurrence of various skin diseases (1,2,4).…”
Section: Introductionmentioning
confidence: 99%